Do determinants of FDI to developing countries differ among OECD investors? Insights from Bayesian Model Averaging - Nikolaos Antonakakis; Gabriele Tondl (FIW - Research Centre International Economics, 2011)
The main objective of this paper is to examine the determining factors of outward FDI from four major OECD investors US, Germany, France and the Netherlands to developing countries located in different world regions. Our goal is to elucidate whether the motivation for FDI differs among these investors. Rather than relying on specific theories of FDI determinants we examine them all simultaneously employing Bayesian Model Averaging (BMA) in a panel data set with 129 FDI destinations in 5 geographical regions over the period 1995-2008. This approach permits us to select the most appropriate model that governs FDI allocation and to distinguish robust FDI determinants. We find that all our investors search for destinations with whom they have established intensive trade relations and that offer a qualified labor force. However, low wages and attractive tax rates are robust investment criteria too, and a considerable share of FDI is still resource-driven. Our investors show fairly similar strategies in the main FDI destinations.
Keywords: C11; F0; F21; 330; FDI determinants; Bayesian Model Averaging; OECD; Developing countries; US; Germany; France; Netherlands